Two murine natural polyreactive autoantibodies are encoded by nonmutated germ-line genes. - Baccala, R (1989)
Two monoclonal IgM natural autoantibodies (E7 and D23) obtained from the fusion of normal, nonimmunized, BALB/c mouse spleen cells and nonsecreting myeloma cells were selected on the basis of their polyreactivity with auto- and xenoantigens and chemical haptens. Nucleotide sequence analysis of the variable and constant regions of the heavy and light chains showed the following. (i) The antibodies arise from different genetic elements with very low or no homology--E7 from a heavy-chain variable region (VH) of family 36-60 and kappa light-chain variable region (V kappa) from a group 19--whereas D23 derives from a VH of family Q52 and V kappa derives from group 8. (ii) E7 and D23 are probably of germ-line origin, as suggested by high homology with VH genes from the unrearranged genome. Compared with the germ-line VH 1210.7 gene, E7 has a single nucleotide difference leading to a silent mutation at position 15, whereas D23 seems to be encoded by germ-line VH 101 with one nucleotide difference causing replacement of Ser-84 by Ala. (iii) The genetic V kappa and VH elements for E7 and D23 also give rise to different responses to phenyloxazolone, dinitrophenyl, 5-(dimethylamino)naphthalene-1-sulfonyl, arsonate, phosphocholine, and influenza virus hemagglutinin. Antibodies from normal and autoimmune mice with rheumatoid factor-like activity are also homologous to E7 and D23. These results indicate that polyreactive autoantibodies are encoded by germ-line genes and that, starting with the preimmune poly- and autoreactive repertoire, mutated forms of antibodies recognizing exogenous antigens can be obtained and selected.